Emerging cervical spine surgery in Chitwan Medical College: A case series - Prajapati, Akesh; Sitaula, Jyoti; Sharma, Bishnu Dev; Shrestha, Sujit; Pant, Pujan (Journal of Chitwan Medical College, 2017)
We report 10 consecutive patients who underwent anterior cervical disectomy and fusion (ACDF) or anterior cervical corpectomy and fusion (ACCF) from Nov 2015. Nine of these patients sustained fracture or dislocation of cervical spine and one patient had tuberculous spondylitis. Eight patients improved by at least one grade (Frankel spinal scoring system) post operatively while 2 patients who had respiratory distress pre-operatively expired on 3rd and 21st post operative day.